Synthesis and T-type calcium channel blocking activity of novel diphenylpiperazine compounds, and evaluation of in vivo analgesic activity - Kam, Yoo Lim; Rhee, Hee-Kyung; Rhim, Hyewhon; Back, Seung Keun; Na, Heung Sik; Choo, Hea-Young Park (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
Novel diphenylpiperazine derivatives were synthesized and evaluated for their inhibitory activity against T-type calcium channel by whole-cell patch clamp recordings on HEK293 cells. Among the test compounds, 2 and 3d were effective in decreasing the response to formalin in both the first and second phases and demonstrated antiallodynic effects in a rat model of neuropathic pain. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: CA2+ CHANNELS; PAIN; RAT; MIBEFRADIL; ALLODYNIA; BLOCKERS; MODEL